Simultaneous Quantification of 11 Phenolic Compounds and Consistency Evaluation in Four Dendrobium Species Used as Ingredients of the Traditional Chinese Medicine Shihu - Zhu, An-Ling; Hao, Jing-Wen; Liu, Lei; Wang, Qi; Chen, Nai-Dong; Wang, Guang-Lin; Liu, Xiao-Quan; Li, Qiang; Xu, Hui-Min; Yang, Wei-Han (Frontiers in Nutrition, 2021)
The interchangeable use of different herbs to prepare the same formulation is a common practice in Traditional Chinese Medicine (TCM). However, this practice would require the component herbs to share similar compositions, at least in terms of the bioactive agents, to ensure they can replace each other in drug preparation. In this paper, we developed an effective and comprehensive high-performance liquid chromatography-diode array detector (HPLC-DAD) method for simultaneous analysis of 11 phenolic compounds in the methanol extracts of Dendrobium huoshanense, Dendrobium nobile, Dendrobium chrysotoxum, and Dendrobium fimbriatum, which have been identified as interchangeable ingredients for the same TCM preparation “Shihu” in the Chinese pharmacopoeia (ChP). The consistency of the four Dendrobium species was evaluated on the basis of the presence of the 11 investigated compounds and the HPLC fingerprints of the plants’ methanol extracts. When gradient elution was performed with a solvent system of acetonitrile and water on a Zorbax Eclipse XDB-C18 (150 × 4.6 mm, 5 μm) with monitoring at 220 nm, all 11 investigated compounds were isolated at the baseline. The established HPLC method showed excellent linearity (all analytical curves showed relative coefficients [R2] > 0.999), sensitivity, precision (relative standard deviation [RSD] < 2%), and accuracy (recovery, 90.65%~99.17%). These findings confirmed that the method we constructed was reliable. Quantification analysis showed significant differences in the contents of the investigated polyphenols in the four Dendrobium species. Evaluations of consistency revealed that the similarities among the four species was 0.299-0.906 in assessments based on the 11 polyphenols, and 0.685-0.968 in assessments based on HPLC fingerprints. Thus, the components of the four Dendrobium species may be significantly different, and more experiments are required to determine whether they can be used interchangeably in the same amounts for preparing the formulation according to ChP.